Information technology of detection viewpoint of camera of unmanned aerial vehicle - Нічіков, Є. П.; Чирков, А. В. (Problems of Informatization and Control, 2015)
An information technology of detection viewpoint of camera of unmanned aerial vehicle developed.Software architecture allows receive input data for the implementation of the proposed methods bothfrom local sources (ie local video files and logs of telemetry) and from the cameras and unmannedaerial vehicle sensors or from simulator